Why segment the maxilla between laterals and canines? - Lucas Senhorinho Esteves; Jean Nunes dos Santos; Steven M. Sullivan; Luana Maria Rosário Martins; Carolina Ávila (Dental Press Editora, 2016)
Introduction: Maxillary surgery on a bone segment enables movement in the sagittal and vertical planes. When performed on multiple segments, it further provides movement in the transverse plane. Typical sites for interdental osteotomies are between laterals and canines, premolars and canines, or between incisors. Additionally, osteotomies can be bilateral, unilateral or asymmetric. The ability to control intercanine width, buccolingual angulation of incisors, and correct Bolton discrepancy are some of the advantages of maxillary segmentation between laterals and canines. Objective: This article describes important features to be considered in making a clinical decision to segment the maxilla between laterals and canines when treating a dentoskeletal deformity. It further discusses the history of this surgical approach, the indications for its clinical use, the technique used to implement it, as well as its advantages, disadvantages, complications and stability. It is therefore hoped that this paper will contribute to disseminate information on this topic, which will inform the decision-making process of those professionals who wish to make use of this procedure in their clinical practice. Conclusions: Segmental maxillary osteotomy between laterals and canines is a versatile technique with several indications. Furthermore, it offers a host of advantages compared with single-piece osteotomy, or between canines and premolars.